Regulation of transport processes across the tonoplast - Neuhaus, H. Ekkehard; Trentmann, Oliver (Frontiers in Plant Science, 2014)
In plants, the vacuole builds up the cellular turgor and represents an important component in cellular responses to diverse stress stimuli. Rapid volume changes of cells, particularly of motor cells, like guard cells, are caused by variation of osmolytes and consequently of the water contents in the vacuole. Moreover, directed solute uptake into or release out of the large central vacuole allows adaptation of cytosolic metabolite levels according to the current physiological requirements and specific cellular demands. Therefore, solute passage across the vacuolar membrane, the tonoplast, has to be tightly regulated. Important principles in vacuolar transport regulation are changes of tonoplast transport protein abundances by differential expression of genes or changes of their activities, e.g., due to post-translational modification or by interacting proteins. Because vacuolar transport is in most cases driven by an electro-chemical gradient altered activities of tonoplast proton pumps significantly influence vacuolar transport capacities. Intense studies on individual tonoplast proteins but also unbiased system biological approaches have provided important insights into the regulation of vacuolar transport. This short review refers to selected examples of tonoplast proteins and their regulation, with special focus on protein phosphorylation.